2013
DOI: 10.1515/hf-2012-0184
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and kraft pulping of seven hybrid aspen clones. Dimension measurements on the vessels and UMSP of the cell walls

Abstract: Micropropagated hybrid aspen clones (Populus tremuloides Michx.×Populus tremula L.) and a plus-tree (superior phenotypes selected) aspen (Populus tremula L.) were grown under similar conditions in the central part of Latvia. After cutting at the age of 12 years, 64 sample trees were examined. The dimensions of the vessels and the content of cellulose, lignin, extractives and ash were determined. The cell walls were characterised by UV microspectrophotometry (UMSP) in the UV range. The dimensions of fibres obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…5). The fiber characteristics were qualitatively similar to those found in previous studies [42,46]. Also DeBell et al [46] showed an increasing trend in fiber lengths from pith to bark.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…5). The fiber characteristics were qualitatively similar to those found in previous studies [42,46]. Also DeBell et al [46] showed an increasing trend in fiber lengths from pith to bark.…”
Section: Discussionsupporting
confidence: 89%
“…However, clearly speciesspecific factors such as a different ratio of cell wall thickness to diameter influenced the differences, since the wall thicknesses were around 1-2 μm in the study of Werdin et al [14], while they were around 6 μm in the current study. On the other hand, wood density is largely controlled by cell wall thicknesses and diameters within different species [14,[42][43][44][45].…”
Section: Impacts Of Clonal Differences and Within-tree Heterogeneitymentioning
confidence: 99%
“…The planting design of this experiment was: block plots for 25 trees (block size 5 × 5 plants), planted by 3 × 3 m in 3 to 5 replications. Seven aspen hybrid clones (Sable et al, 2013b) -eight sample trees for each clone -were selected for this study. Aspen and hybrid aspen were cut at the age of 19-20 years.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, it has been investigated also from the chemical composition point of view -as a source of different lignins and their derivatives (Kim et al, 2013); thermal decomposition of poplar wood was studied with the aim to convert solid biomass mainly into a liquid product known as bio-oil (Dong et al, 2012). Aspen and hybrid aspen wood and fi bres were studied as a source for the pulp and paper industry both in Latvia (Sable et al, 2012b(Sable et al, , 2013a(Sable et al, , 2013bTreimanis et al, 2006;Zeps et al, 2008Zeps et al, , 2012 and other countries (Francis et al, 2006;Tullus et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Under temperate and hemiboreal conditions, hybrid aspen ( Populus tremula L. × P. tremuloides Michx. ), which shows superior growth compared to local and introduced tree species [ 3 ] is one of the most promising alternatives for multipurpose commercial forestry, providing services from timber production to bioremediation [ 4 , 5 , 6 ]. The superiority of the hybrids can be stable across different growing condition because of heterosis [ 7 , 8 ], which interactively amplifies the expression of certain traits exceeding those of parental plants [ 9 ].…”
Section: Introductionmentioning
confidence: 99%